Harnessing the immune system in the treatment of cutaneous T cell lymphomas - Fay, Christopher J.; Awh, Katherine C.; LeBoeuf, Nicole R.; Larocca, Cecilia A. (Frontiers in Oncology, 2023)
Cutaneous T cell lymphomas are a rare subset of non-Hodgkin’s lymphomas with predilection for the skin with immunosuppressive effects that drive morbidity and mortality. We are now appreciating that suppression of the immune system is an important step in the progression of disease. It should come as no surprise that therapies historically and currently being used to treat these cancers have immune modulating functions that impact disease outcomes. By understanding the immune effects of our therapies, we may better develop new agents that target the immune system and improve combinatorial treatment strategies to limit morbidity and mortality of these cancers. The immune modulating effect of therapeutic drugs in use and under development for cutaneous T cell lymphomas will be reviewed. Capsule summary: • Several therapeutic drugs in use and under development for cutaneous T cell lymphomas have immune modulatory effects • Novel combinatorial treatment strategies have been developed based on the latest understanding of the favorable immune effects of individual therapies